Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/twec.12783
|View full text |Cite
|
Sign up to set email alerts
|

Capital flows to Asia and Latin America: Does institutional quality matter?

Abstract: Using a sample of 28 emerging market economies from Asia and Latin America spanning 1990–2013, we show that the marginal effect of capital flows on growth is positive and contingent on the threshold level of institutional quality (IQ). The conditional effect of capital flows holds for both the income per capita growth and total factor productivity (TFP) growth. We also determine the different threshold levels of IQ at which the marginal effect of capital flows is positive. The overall level of IQ in the Asian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 86 publications
1
6
0
Order By: Relevance
“…In other words, the impact of the size of the country and FX turnover on the issuance of local currency debt is stronger as the quality of institutions improves for values of Governance above the median (> 50th percentile). This is consistent with the literature on the amplifying role of the Governance index (Arya et al, 2019 ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In other words, the impact of the size of the country and FX turnover on the issuance of local currency debt is stronger as the quality of institutions improves for values of Governance above the median (> 50th percentile). This is consistent with the literature on the amplifying role of the Governance index (Arya et al, 2019 ).…”
Section: Resultssupporting
confidence: 93%
“…By construction, the Governance index ranges from − 5 (weak quality) to + 5 (strong quality). Strong institutions may improve the development of the private sector and its funding by financial markets and pull foreign investors on local currency debt (Arya et al, 2019 ; Claessens et al, 2007 ; Eichengreen et al, 2002 ; Osina, 2021 ).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Third, although the acquirer's acquisition experience has received considerable research interests in investigating the completion of CBAs from developed market firms (Collins et al., 2009; Dikova et al., 2010; Lim & Lee, 2016), some studies have questioned the applicability of the conclusions derived from developed market settings in emerging market context (Arya et al., 2019; Bhaumik et al., 2018; Dikova et al., 2010; Liou et al., 2016; North, 1990; Pinto et al., 2017; Rui & Yip, 2008). As such, based on the above framework, we further highlight our focus on the impacts of acquisition experience on CBAs by EMFs and incorporate consideration of institutional quality in the host country in our analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Based on an index of risk of expropriation, their study showed that in countries where the level of institutional effectiveness was low, an increase in capital was detrimental to growth, as the additional capital resulted in rent seeking and fruitless ventures. In a study involving a set of 28 emerging countries over the period 1990–2013, Arya, Banerjee and Cavoli (2019) found that the ability of capital flows to have a positive impact on both gross domestic product (GDP) per capita and total factor productivity was contingent of the threshold level of institutional quality. Slesman, Baharumshah and Wohar (2015) noted a robust positive relationship between measures of capital flows and economic growth for countries with institutional quality above a certain threshold.…”
Section: Introductionmentioning
confidence: 99%